SISTEM INFORMASI GEOGRAFIS PERSEBARAN PENYAKIT DIARE DI KABUPATEN TEGAL PADA TAHUN 2020-2022 - MUHAMAD RAIKHAN ILHAM FIRMANSYAH; Bambang Agus Herlambang; Ahmad Khoirul Anam (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Diarrhea is a disease of major concern throughout the world. Diarrhea is still a big problem for public health in developing countries, including Indonesia. Tegal Regency itself is also facing cases of this diarrheal disease, it can be seen from the data that cases in Tegal Regency District have decreased from 2020 to 2022. Margasari District shows that the number of cases in 2020 was 1481 and experienced a decrease in 2021 to 2022 by 1208 (2021) and 1131 (2022). Meanwhile, Slawi District itself recorded a rise and fall in the number of diarrhea cases. This needs to be highlighted to improve prevention programs so that diarrheal disease does not continue to increase. Research methods are processes or steps for collecting scientific information. This research focuses more on spatial analysis of the maps created and cartographic aspects. The data collection method in this research uses secondary data from BPS Tegal Regency. This data will be entered into Quantum GIS software to obtain a map image that shows the desired information. The Geographic Information System approach can provide information about the factors and causes of diarrheal disease. It is necessary to collaborate between various sectors to provide health services for the community and increase awareness of the increase in cases of diarrhea in work areas that are far from the reach of services. In this way, it is hoped that it can reduce the incidence of diarrheal disease in Tegal Regency and improve overall public health